Effects of the CrossFit Exercise Data Analysis on Body Composition and Blood Profiles - Eun-Ju CHOI; Wi-Young SO; Taikyeong Ted. JEONG (Tehran University of Medical Sciences, 2017)
Effects of the CrossFit Exercise Data Analysis on Body  Composition and Blood Profiles